Review on Pre-clinical Antimicrobial Assay - Febrimarsa, Febrimarsa (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Pre-clinical antimicrobial testing is one costly step in antimicrobial drugs development. Costly effective methods in performing the in vitro and in vivo assay as part of pre-clinical stage is critical. We reviewed the current development of this stage. We found that standardization of agar diffusion techniques and measurement of minimal inhibitory concentrations in broth dilution methods serve as the primary reference for in vitro antimicrobial testing. In vivo, moral issues, ethics, costs, and the correlation of using animal models with human physiological conditions enforce us to seek alternative systems or animal models. Organ-on-a-Chip (OC) emerges as an ethically sound alternative system, yet in terms of cost and simulation of physiological conditions, there is still much progress to be made. Fruit fly (Drosophila melanogaster) and waxmoth (Galleria mellonella) are currently the main alternative animal models that are more affordable, simple, and ethically sound compared to worms, silkworms, mice, and primates. Artemia spp. and Hydractinia spp. have the potential to become new alternative animal models in simulating microbial infections and the efficacies of the antimicrobial that fight against it in the future.